Effect of Variation in the Number of Blades on Turbine Rotation and Output Power at PLTPH (Picohydro Power Plant) Using a Kaplan Turbine - Arnawan Hasibuan; Asran Asran; Sartika Yanti; Misbahul Jannah; Andik Bintoro; Ari Nrartha (Indonesian Scientific Journal, 2023)
The turbine can be a component that plays an important role as an energy converter that produces power in a picohydro power plant (PLTPH). The turbine used in this study is the Kaplan Turbine. The Kaplan turbine is a type of reaction turbine with a head of 1.58 m. This research examines the effect of variations in the number of blades on turbine rotation and output power in pico-hydro power plants (PLTpH) using Kaplan turbines so that voltage, current, power can be generated which affect the torque value and the efficiency obtained in the PLTpH prototype. This study aims to obtain a turbine runner with the number of blades that can produce the highest efficiency, so a variation of the Kaplan turbine runner is made with a number of blade runner variations, namely 4 blades, 6 blades, and 8 blades. The results showed that the addition of the number of blades produced the highest output with the number of blades 6 which produced a turbine rotation of 218.1 Rpm, generator rotation of 2433 Rpm, generator voltage of 19 volts, generator power of 1900 watts, and torque of 17.5 Nm. Nilai efesiensi yang dihasilkan yaitu 26,62 %. The results of this research are expected to be a reference and help improve human resources to develop power plants in rural areas, and open up opportunities for the community to develop small-scale power plants, namely pico-hydro power plants.